Medial Collagen Type and Quantity Influence Mechanical Properties of Aneurysm Wall in Bicuspid Aortic Valve Patients - Neave, Louise; Tahir, Maria; Nightingale, Miriam; Jadli, Anshul S.; Patel, Vaibhav B.; Barker, Alexander J.; Malaisrie, S. Chris; McCarthy, Patrick M.; Markl, Michael; Fedak, Paul W. M.; Di Martino, Elena S. (Frontiers in Mechanical Engineering, 2022)
Collagen has an essential role in aortic biomechanics, and collagen remodeling has been associated with the development and progression of aortic aneurysm. However, the exact mechanisms behind collagen remodeling and the biomechanical implications are not well understood. This study presents an investigation of the relationship between collagen remodeling in the aortic wall and biomechanics, by means of collagen assays, smooth muscle cell gene expression, and mechanical testing on human aortic specimens collected from patients with bicuspid aortic valve. Collagen assay analysis was employed to determine collagen-I and total collagen content; quantitative real-time PCR was used to determine amounts COL1A1 and COL3A1 expression in the tissue. These parameters were compared with the local biomechanical properties determined from biaxial and uniaxial tensile testing. Collagen-I content was found to relate to increased mechanical properties, while total collagen content did not exhibit a relationship with biomechanics. COL1A1 and COL3A1 expression were found to relate more strongly to the biomechanical properties of the tissue than the collagen contents, with increased expression in the tissue associated with reduced biomechanical performance. Relationships between all variables appeared strongest in the medial layer of the aortic wall. The effect of age is also noted, as the collagen content seemed to relate more strongly to the biomechanical properties of older patients than it did in younger patients. Findings highlight the importance of type and location in determining the influence of collagen on aortic biomechanics, as well as the role of gene expression in the onset and progression of collagen remodeling in aortic aneurysm.